2020
DOI: 10.3389/fpsyg.2020.00811
|View full text |Cite
|
Sign up to set email alerts
|

No Robust Effect of Distributed Practice on the Short- and Long-Term Retention of Mathematical Procedures

Abstract: We investigated the effect of distributed practice and more specifically the "lag effect" concerning the retention of mathematical procedures. The lag effect implies that longer retention intervals benefit from longer inter-study intervals (ISIs). University students (N = 235) first learned how to solve permutation tasks and then practiced this procedure with an ISI of zero (i.e., massed), one, or 11 days. The final test took place after one or five weeks. All conditions were manipulated between-subjects. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Some indirect evidence suggests that the mathematics spacing effect can shrink or disappear if the spacing gap is much shorter than the test delay, as is the case with non‐mathematics materials (e.g., see meta‐analysis by Cepeda et al, 2006). This possibility also is consistent with the results of the mathematics spacing study that found null effects when the test delay was rather long (Ebersbach & Barzagar Nazari, 2020a). Students in that study either massed their practice or spaced their practice across two sessions separated by 1 or 11 days before taking a test 5 weeks later, and the larger spacing gaps produced larger test scores: about 25% after massed practice, about 30% after a 1‐day spacing gap, and nearly 40% after an 11‐day spacing gap.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Some indirect evidence suggests that the mathematics spacing effect can shrink or disappear if the spacing gap is much shorter than the test delay, as is the case with non‐mathematics materials (e.g., see meta‐analysis by Cepeda et al, 2006). This possibility also is consistent with the results of the mathematics spacing study that found null effects when the test delay was rather long (Ebersbach & Barzagar Nazari, 2020a). Students in that study either massed their practice or spaced their practice across two sessions separated by 1 or 11 days before taking a test 5 weeks later, and the larger spacing gaps produced larger test scores: about 25% after massed practice, about 30% after a 1‐day spacing gap, and nearly 40% after an 11‐day spacing gap.…”
Section: Discussionsupporting
confidence: 89%
“…This potential caveat is only conjecture, however, because the nature or degree of feedback has not been manipulated in a mathematics spacing study. However, feedback was provided after only one half of the practice problems in the aforementioned study finding only null effects (Ebersbach & Barzagar Nazari, 2020a).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations